COMPANY INCOME TAX (CIT) REFORM AND INTERNALLY GENERATED REVENUE IN NIGERIA (Journal of Global Accounting, 2022)
The main objective of this study is to evaluate the effect of CIT reforms on internally generated revenue in Nigeria from 2004 to 2019. Data were extracted from Central Bank Statistical Bulletin. The study employed regression analysis to test the formulated hypothesis with aid of E-View 9.0. Based on the data analyzed, the study revealed that Company Income Tax (CIT) has a significant effect on internally generated revenues in Nigeria. Based on the finding the study, the researchers recommended that there should be continuous review and reforms in the Nigeria company income tax to reflect the current realities of the modern economy since tax reform was found to have significant effect on revenue performance.
Keywords: Central Bank of Nigeria, CIT reforms; internally generated revenue; Nigerian economy